2021
DOI: 10.1108/apjml-04-2021-0276
|View full text |Cite
|
Sign up to set email alerts
|

Big Five personality traits and green consumption: bridging the attitude-intention-behavior gap

Abstract: PurposeThis study examines the roles of Big Five personality traits, including conscientiousness, agreeableness, extraversion, neuroticism and openness to experience, in shaping green consumption behavior, as well as bridging the attitude-intention-behavior gap in environmentally friendly consumption and testing the gender differences between these associations.Design/methodology/approachA dataset of 611 consumers was collected by means of mall-intercept surveys in major Vietnamese cities. Structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 69 publications
(274 reference statements)
8
81
1
3
Order By: Relevance
“…Specifically, the significant relationship of attitudes towards green products' purchase intention is in line with the findings of Duong (2022), Nguyen and Nguyen (2021), and Taufique and Islam (2021). This finding showed that consumers' perceptions towards green products are crucial to cultivate their purchase intention, as the consumers are likely to purchase green products if they have favourable and/or positive attitudes towards them.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Specifically, the significant relationship of attitudes towards green products' purchase intention is in line with the findings of Duong (2022), Nguyen and Nguyen (2021), and Taufique and Islam (2021). This finding showed that consumers' perceptions towards green products are crucial to cultivate their purchase intention, as the consumers are likely to purchase green products if they have favourable and/or positive attitudes towards them.…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…Besides, five items of environmental consciousness were derived from (Xu et al, 2020). Lastly, the green product's purchase intention is measured with five items borrowed from (Duong, 2022). Therefore, a total of 23 items were used to measure the five constructs in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Former studies explored the reasons for the development of green marketing, which were the outcomes of ecological pressures and the proposal of the idea of sustainable consumption; besides, studies also explored the significance of green marketing in sustainable consumption (Chen, 2016). From the consumers’ perspective, green marketing can balance limited resources and unlimited consumer demands or needs, and it is beneficial to enhance consumers’ sustainable consumption conscience (Duong, 2022; Yu et al, 2019). From the enterprises’ perspective, green marketing is helpful to help firms change organizational behaviors to be more environmentally friendly and more sustainable; for instance, companies may reduce waste disposals, improve recycling efficiency, develop new technologies and use more environmentally friendly materials, thus producing sustainable products for consumption (Ball & Kittler, 2019).…”
Section: Introductionmentioning
confidence: 99%